A sourcebook of early modern European history
1 online resource.
Keywords: "A Sourcebook of Early Modern European History not only provides instructors of early modern European history with primary sources of a manageable length and translated into English, it also provides students with a concise explanation of their context and meaning.It is ideal for students of early modern history, and of early modern Europe in particular"--